DISPENSASI UMUR PERKAWINAN SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 01 TAHUN 1974 TENTANG PERKAWINAN - M. Syaifur Rohman; Sholihan Sholihan; Muwahid Muwahid (MIMBAR YUSTITIA, 2020)
Marriage dispensation is regulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. with considerations and reasons for not meeting the requirements for the age of marriage as determined by the applicable laws and regulations. This study aims to fulfill the general provisions regarding marriage according to Law Number 16 of 2019 concerning Marriage, and want to know how the implementation of the provision of marriage dispensation based on the provisions of Article 7 paragraph (2) of Law Number 16 of 2019 concerning Marriage. From the main results of the research, it can be concluded that Law Number 16 of 2019 concerning Marriage adheres to the principle that a prospective husband and wife must have enough body and soul so that there is a regulation on the marriage age limit for men or women who must be 19 years old. The granting of a marriage dispensation for a prospective husband or wife who has not reached the age limit for marriage can be submitted by the parents (guardians) of the prospective husband or wife to the Religious Court in the applicant's jurisdiction. The dispensation application can be granted by the judge if there is a reason that the relationship between the prospective husband and the prospective wife does not deviate from the religious norms they adhere to.